Mucinous Carcinoma, Mucinous Borderline Tumor and Pseudomyxoma Ovarii in a Cystic Teratoma: A Histological Conundrum - Cinzia Giacometti; Mariateresa Mirandola; Camillo Aliberti; Filippo Molinari; Lisa Marcolini; Daniele Mautone; Guido Martignoni (Diagnostics)
Mature teratomas account for approximately 20% of all ovarian tumors identified in pathological studies. Benign or malignant somatic neoplasms developing within teratomas can arise from any tissue in up to 2% of mature cystic teratomas, including low-grade malignant mucinous neoplasms. This report presents the case of a 34-year-old woman with no previous gynecological or general health issues, who was admitted to our Hospital after an asymptomatic pelvic mass was detected during a routine exam. A transvaginal ultrasound revealed a unilateral pelvic mass in the left adnexal region, measuring 8 cm. The CT scan showed a cystic-appearing formation measuring nearly 12 cm, which indented the bladder dome. Final diagnosis indicated a mucinous carcinoma arising from a mucinous borderline lesion within the context of a mature ovarian teratoma. No other involvement or lymphadenopathies were detected on 18FDG-PET CT scan, and the patient is now well and free of recurrences.